Staff and patient experience of improving access to psychological therapy group interventions for anxiety and depression. (2013) - Newbold, Alexandra; Hardy, Gillian; Byng, Richard
Abstract : Background: The improving access to psychological therapy (IAPT) initiative aims to provide widespread evidence-based psychological treatments for common mental health problems in the UK. Individual services have implemented National Institute for Clinical Excellence guidelines in various ways; some provide group-based therapy, whilst others do not. Aims: The study investigates how patients and staff experience group-based therapy, what they find helpful and where improvements can be made. Method: Forty-five semi-structured interviews were undertaken with staff and patients in three IAPT services. Framework analysis was used to analyse comments relating to patient experience in group-based treatment. Results: The study found that patients can feel isolated with their symptoms and group-based interventions can normalise the illness, reducing stress. Individuals experience benefits and, in some cases, difficulties, in different ways. Some patients hear of the strategies that others have found useful, and observe others' progress, which may bring hope for their own recovery. Conclusions: IAPT group-based interventions appear to aid recovery in different ways to one-to-one therapy, by normalising mental illness and increasing social contact. Greater understanding of the factors operating in group-based interventions might increase attendance and recovery facilitated by IAPT group interventions.